Efektifitas Penggunaan Explosion Box Dalam Meningkatkan Sosial Emosional Anak Usia Dini di Raudlatul Athfal Muslimat NU 81 Nurul Falah Banjarsari - Khasanah, Nur Fikriyatul; Maarif, Nina Nuriyah; Fithriyah, Kais Nabila (Atthiflah: Journal of Early Childhood Islamic Education, 2025)
Early childhood education primarily aims to support the physical and psychological development of children outside the home environment before they enter elementary school. At this stage, key areas of development include motor skills, cognitive abilities, language, and social-emotional growth. This study explores the use of "explosion box" play media as a tool to promote the social-emotional development of children aged 5–6 at RAM NU 81 Nurul Falah Banjarsari, Gresik. Using qualitative research methods, the findings indicate that explosion boxes can effectively enhance children's social-emotional skills, which are crucial for their ability to interact with the broader social environment.